Analisis Implementasi Label Halal pada Produk Usaha Mikro Kecil Menengah Makanan Mie Setan di Desa Pakong Persfektif Undang-Undang No. 33 Tahun 2014 - Hasanah, Uswatun; Nasik, Khoirun (Hikmah, 2024)
Pakong Village is a village where the entire community adheres to Islam, where the population is increasing day by day. This increase in population is very influential, one of which is in the food industry, so that consumer demand is increasing and the types of food offered are also diverse. However, it is not uncommon for producers to lack understanding of the importance of product labeling. This research aims to find out the types of haram and halal food in terms of ingredients and processing, as well as analyze related halal certification and halal label status on devil noodle products which are currently a favorite of various circles of society. This research uses a qualitative method with an empirical juridical approach. Data were collected through observations and interviews with several consumers and producers. The results show that some producers still have not applied the halal label correctly, which has resulted in concerns among Muslim consumers. Consumer responses indicate that there is a demand to immediately change the product name to reflect its halalness. The impact of this research is to provide benefits for producers in improving compliance with halal standards and for consumers in ensuring the halalness of the products consumed, as well as being a learning material for various related parties